2020
DOI: 10.1002/ps.5729
|View full text |Cite
|
Sign up to set email alerts
|

Triazophos‐induced vertical transmission of rice stripe virus is associated with host vitellogenin in the small brown planthopper Laodelphax striatellus

Abstract: BACKGROUND Rice stripe virus (RSV) is one of the most serious rice diseases in East Asia. The small brown planthopper (SBPH), Laodelphax striatellus, is an economically important rice pest. SBPH transmits RSV horizontally and vertically, resulting in serious rice economic losses. Exposure to sublethal doses of insecticides can induce many physiological and cellular changes in insects. However, the mechanism underlying triazophos‐induced RSV vertical transmission remains unclear. Here, we investigated the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(175 reference statements)
1
7
0
Order By: Relevance
“…Thus, our study measured the expression levels of RNA3 and CP, and they were both up-regulated significantly by the LC 10 dose of imidacloprid, whereas decreased by the LC 30 dose of imidacloprid. These results are generally consistent with the recent study which showed that after treatment with LC 20 to LC 50 of triazophos, the transcript levels of RNA3 and CP were significantly stimulated in the RSV-carrying SBPH [50]. These results showed that low concentrations of insecticides could increase RSV viral load in viruliferous SBPH.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, our study measured the expression levels of RNA3 and CP, and they were both up-regulated significantly by the LC 10 dose of imidacloprid, whereas decreased by the LC 30 dose of imidacloprid. These results are generally consistent with the recent study which showed that after treatment with LC 20 to LC 50 of triazophos, the transcript levels of RNA3 and CP were significantly stimulated in the RSV-carrying SBPH [50]. These results showed that low concentrations of insecticides could increase RSV viral load in viruliferous SBPH.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that the transcript level of Vg and VgR was up-regulated in insects exposed to sublethal doses of insecticides. In SBPH, Vg and VgR mRNA expressions were increased in the females exposed to sublethal doses of triazophos [50]. In Nilaparvata lugens, the transcript level of Vg was significantly increased by low doses of deltamethrin and triazophos [59].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the laboratory, SBPH was reared using the rice variety Wuyujing-3, provided by China National Rice Research Institute, Hangzhou, China. SBPH were reared continuously in the laboratory and were raised in plastic frame cages (50 cm (L): 50 cm (W): 30 cm (H)) in an artificial climate chamber (27 ± 1 • C, 70-80% (RH) and 14:10 h light: dark (L:D)) on paddy seedlings (10 ± 5 days) [52]. Cages were made of nylon mesh cloth, having a zippered entrance on one side.…”
Section: Plant and Insectmentioning
confidence: 99%